2019
DOI: 10.1007/s10570-019-02888-x
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected microphase transitions in flow towards nematic order of cellulose nanocrystals

Abstract: Organization of nanoparticles is essential in order to control their light-matter interactions. We present cellulose nanocrystal suspension organization in flow towards a unidirectional state. Visualization of evolving polarization patterns of the cellulose nanocrystal suspensions is combined with steady and oscillatory shear rheology. Elucidation of the chiral nematic mesophase in a continuous process towards unidirectional order enables control of alignment in a suspension precursor for structural films and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…[ 33 ] This is an indication that the rheological material response in both phases is dominated by the interaction between the self‐assembled structures. [ 34 ] The moduli from strain sweep tests are presented in Figure 2b, for an angular frequency of 1.0 rad s −1 . From a quantitative point of view, the dynamic moduli in the linear viscoelastic region (≈<0.1%) correspond to the frequency sweep data in Figure 2a, confirming again the gel‐like material response.…”
Section: Resultsmentioning
confidence: 99%
“…[ 33 ] This is an indication that the rheological material response in both phases is dominated by the interaction between the self‐assembled structures. [ 34 ] The moduli from strain sweep tests are presented in Figure 2b, for an angular frequency of 1.0 rad s −1 . From a quantitative point of view, the dynamic moduli in the linear viscoelastic region (≈<0.1%) correspond to the frequency sweep data in Figure 2a, confirming again the gel‐like material response.…”
Section: Resultsmentioning
confidence: 99%
“…In contradistinction, the larger viscosity of the non-sonicated suspensions in the biphasic regime investigated here locks the alignment of CNC. Microphase transitions in flow towards the nematic order of CNC suspensions showing shear thinning behavior have been reported [ 36 ]. However, shear-thinning behavior of CNC suspensions does not ensure alignment of nanocrystals, but a breakup of CNC aggregates might appear [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, FIB measurement has also been used to analyze cellulose nanocrystals (CNCs), and CNC birefringence patterns using the crossed-Nicol method have been reported [11][12][13][14] . Kádár et al 14) reported birefringence patterns as being sensitive to flow-induced structural changes, thus FIB measurement is considered to be an essential tool for examining the flow-induced structure of CNC suspensions. Tanaka et al 10) developed a highly sensitive apparatus for oscillatory FIB measurement and succeeded in measuring a low-bire-fringent suspension of cellulose nanofibers.…”
Section: Couette Flowmentioning
confidence: 99%